Home » Past Questions » Mathematics » If p-2g + 1 = g + 3p and p - 2 = 0, find g

If p-2g + 1 = g + 3p and p - 2 = 0, find g


Question

If p-2g + 1 = g + 3p and p - 2 = 0, find g

Options

A) -2

B) -1

C) 1

D) 2

The correct answer is B.

Explanation:

p - 2g + 1 = g + 3p.........(1)

p - 2 = 0 .........(2)

From (2), p = 2; put p = 2 into (1);

2 - 2g + 1 = g + 3(2)

3 - 2g = g + 6

-2g - g = 6 - 3

-3g = 3

g = \(\frac{3}{-3}\)

g = -1


More Past Questions:


Dicussion (1)

  • p - 2g + 1 = g + 3p.........(1)

    p - 2 = 0 .........(2)

    From (2), p = 2; put p = 2 into (1);

    2 - 2g + 1 = g + 3(2)

    3 - 2g = g + 6

    -2g - g = 6 - 3

    -3g = 3

    g = \(\frac{3}{-3}\)

    g = -1

    Reply
    Like